The effect of educational units according to the (K.W.L) strategy on the performance of single and group fast attack of handball for students - Kadhem, Abbas Abdulhamza (Jurnal Ilmu Keolahragaan, 2025)
Background. The study explores the impact of educational strategies on students"™ sports performance, focusing on the Know-Want-Learn (K.W.L.) strategy in handball training. Objectives. This research aims to determine the effectiveness of an educational program based on the K.W.L. strategy in enhancing the performance of students in executing single and group fast attacks in handball. Methods. An experimental design was adopted involving identical experimental and control groups, each comprising 20 students (totaling 40). Pre-tests and post-tests were administered to both groups. The experimental group received instruction using the K.W.L. strategy, while the control group followed traditional methods. Data were statistically analyzed using the T-test in SPSS version 20. Results. The findings revealed that the K.W.L. strategy significantly improved the performance of the experimental group in both single and group fast attacks. Additionally, the strategy fostered better student interaction, contributing to the experimental group"™s superiority over the control group. These results support the effectiveness of metacognitive strategies in sports education. Conclusion. The findings of this study confirm that the application of educational units based on the Know"“Want"“Learn (K.W.L.) strategy has a significant positive effect on students"™ performance in both single and group fast attacks in handball. The researcher's most significant recommendations are to encourage individuals participating in the educational process to not confine themselves to traditional methods and approaches and to educate using them.